Definition of main point and content of higher educational establishment students’ research activity in english speaking countries - Сергеєва, О. А. (Scientific notes of the pedagogical department, 2018)
The article presents the points of view of the researchers in the English-speaking countries as to the definition of the essence and content of students’ research activity. It has been established that it is considered as 1) a pedagogical tool that allows supporting and managing the activity of students in the frames of curriculum or their independent work; 2) active pedagogy supporting the process of student research; 3) interaction of a mentor and a student, etc. The main goal of students’ scientific research activity is to improve the level of their training. It is found that students’ research activity must be complex and consistent, and include different methods and means which must be complexified gradually. It has been established that there are different forms of students’ research activities depending on location (classroom activities, extracurricular activities, and activities, which are organized outside the university). Classroom activities include problematic and research tasks on the subject, control and diagnostic tasks in accordance with the curriculum which help develop students’ research approach, accomplish the course work and graduation thesis, perform experimentations, etc.). Extracurricular activities comprise work in students’ scientific groups, creative or research groups according to students and tutors’ scientific interests, participation in students’ scientific conferences of different levels, taking part in grants or contests. As part of research activities, which are organized outside the universities, students meet with key scientists, share experience with students of other educational establishments, participate in international workshops and conferences, collaborate with leading laboratories of scientific and research institutions etc. Students’ research activities are also divided into elementary research work, theoretical research work, and practical research work.